Makna Intensi pada Puisi-Puisi Karya Sutardji Calzoum Bachri - Francisco, Apolo S.; Widyaningrum, Heny Kusuma; Prayoga, Widya Galih (GERAM, 2024)
The study of literary works teaches humans to understand the meaning of life and increases their vision of wisdom and intelligence. Literary works of poetry need to be analyzed with the aim of examining and showing the purpose, message and impression they convey to poetry lovers or readers. The poems entitled "Land of Tears", "Bridge", "But" and "O Youth, Where Are Your Eggs?" Sutardji Calzoum Bachri's work in this research has an intentional meaning. This means that the meaning is the poet's expression of what the poet wants. This method is divided into three stages, namely the data collection stage, the data analysis stage, and the data presentation stage. Sutardji Calzoum Bachri's poems describe the spiritual journey and emotional exploration of humans through strong and imaginative language. His work is able to arouse readers' emotions with the various contradictions and dynamics of life. These poems show sensitivity and deep thoughts towards the world and human life in general. This provides evidence that poetry is a form of real expression that is in process.